The efficiency of Danish banks before and during the crisis: A comparison of DEA and SFA - Andreas Kuchler (Danmarks Nationalbank, 2013)
This paper analyses the development in relative efficiency of Danish banks in the period 2001-2012. Using Data Envelopment Analysis (DEA) and Stochastic Frontier Analysis (SFA) techniques, we find that mean relative efficiency increased during the expansive period 2003-2007, while it decreased during the crisis years 2008-2010. During the recent years, mean relative efficiency increased again, possibly as a result of adjustment of inputs to the reduced output growth as well as the general consolidation in the banking sector. Furthermore, we find a considerable but not perfect correlation between efficiency rankings of banks as estimated by DEA and SFA. Finally, an international benchmarking exercise using data from 203 European banks and banking groups in 2012 shows that larger Danish banks and banking groups, when compared to their peers in other European countries, are distributed largely along most of the spectrum of efficiency.
Keywords: C44; G21; 330; Bank efficiency; DEA; SFA